Novel La(OH)3 integrated sGO-Ag3PO4/Ag Hybrid photocatalyst for sunlight driven ultra-fast degradation of industrial and agricultural pollutants. (February 2022) - Priyanka, Ragam N.; Abraham, Thomas; Plathanam, Neena J.; Joseph, Subi; George, Bini; Mathew, Beena
Abstract: Eco-friendly and economic, sunlight driven photocatalytic degradation of pollutants by semiconductor composites is a prolific technique for water remediation. Herein, we coupled the benefits of rare-earth compound La(OH)3 with sGO-Ag3 PO4 /Ag composite in a facile, room temperature and scalable procedure to enhance the activity to acquire accelerated degradation of organic pollutants of varied structure and significance. Plasmonic silver composites pour electrons to the conduction band of La(OH)3, which by itself is visible light inactive with a large band gap. The electrons from La(OH)3 produce · O2 - which are rapidly converted to highly active ·OH, which are otherwise not produced in sGO-Ag3 PO4 /Ag catalytic system. In addition, integration of rod shaped La(OH)3 leads to a decrease in band gap and thus increased sunlight consumption. Methylene blue and rhodamine B degraded instantaneously while other dyes in few minutes with around 99% mineralization. 4-Chlorophenol and thiram were degraded within 1 and 2 h with 92% and 88% mineralization. The novel composite was 19 times efficient than bare Ag3 PO4 was found exceptionally efficient, stable and recyclable up to four cycles. sGO sheet, AgNPs and La(OH)3 rods carry away the electrons from Ag3 PO4 to prevent photocorrosion to a great extent and thus provide stability. Graphical abstract: Image 1 Highlights: Facile fabrication of stable and recyclable La(OH)3 doped sGO-Ag3 PO4 /Ag. sGO, AgNPs and La(OH)3 prevent recombination and photocorrosion, Ag3 PO4 /Ag activated sunlight inactive La(OH)3 . La(OH)3 furnished ·OH, red shifted absorbance, improved charge transport. Ultrafast mineralization of cationic and anionic dyes (1-4 min) thiram and 4-CP (1-2 h). Superior catalytic activity under sunlight was found over most of the recent composites.